Model‐informed drug development of voxelotor in sickle cell disease: Population pharmacokinetics in whole blood and plasma. (21st April 2022) - Savic, Radojka M.; Green, Michelle L.; Jorga, Karin; Zager, Michael; Washington, Carla B.
Abstract: Oxbryta (voxelotor) is a small‐molecule inhibitor of sickle hemoglobin (Hb) polymerization approved for patients with sickle cell disease (SCD) aged greater than or equal to 12 years at a dose of 1500 mg once daily (q.d.). Voxelotor binds preferentially to Hb, and voxelotor partitioning into red blood cells is an effective predictor of Hb occupancy. The objectives of these analyses were to develop a population pharmacokinetic (PopPK) model for voxelotor in both plasma and whole blood in adults and adolescents to support the dose selection for optimal target engagement and to identify covariates that have a significant effect on voxelotor pharmacokinetics (PK) in plasma and whole blood. An integrated plasma and whole blood PopPK model with two compartments, first‐order absorption and elimination, and a site‐of‐action effect compartment adequately described the concentration‐time profiles of voxelotor in plasma and whole blood in patients treated up to 72 weeks. Covariates with significant effects on voxelotor PK included baseline blood volume on apparent volume of the central compartment and time‐varying hematocrit and dose on whole blood partitioning, indicating that clinical markers of voxelotor effect can, in turn, influence its PK. Furthermore, the model confirmed that voxelotor PK in plasma and whole blood is linear with dose and time and comparable for adults and adolescents. No clinically important covariate effects on voxelotor PK that warranted dose adjustment were identified in this analysis. Overall, the PopPK analyses contributed significantly to the voxelotor label and support 1500 mg q.d. as the therapeutic dose in adults and adolescents with SCD.